2018
DOI: 10.17309/tmfv.2018.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Movement Coordination: Factor Structure of Development in 5th-7th Grade Girls

Abstract: The study objective is to determine the structure of coordination abilities development in 5 th -7 th grade girls. materials and methods. The participants in the study were 5 th grade girls (n = 20), 6 th grade girls (n = 23), 7 th grade girls (n = 19). The study used the following methods: analysis and collation of scientific and methodological literature, general scientific methods of theoretical level, such as analogy, analysis, synthesis, abstraction, induction, as well as general scientific methods of emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
(10 reference statements)
2
10
0
Order By: Relevance
“…Reliable interconnection of the average level between the integral indicator of coordination preparedness and the indicator of proprio-receptive functions can be regarded as a fact of kinesthesia (muscle sensation) significance in the structure of coordination readiness of volleyball players (girls) at the age of 15-17. The results obtained by us confirmed the experimental data of other authors (Ivashchenko et al, 2018;Malikova, Doroshenko, Symonik, Tsarenko, & Veritov, 2018), on the greater kinesthesia significance for females compared to males.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Reliable interconnection of the average level between the integral indicator of coordination preparedness and the indicator of proprio-receptive functions can be regarded as a fact of kinesthesia (muscle sensation) significance in the structure of coordination readiness of volleyball players (girls) at the age of 15-17. The results obtained by us confirmed the experimental data of other authors (Ivashchenko et al, 2018;Malikova, Doroshenko, Symonik, Tsarenko, & Veritov, 2018), on the greater kinesthesia significance for females compared to males.…”
Section: Discussionsupporting
confidence: 91%
“…The correlation of kinesthesia and coordination abilities indicators was confirmed (Ivashchenko et al, 2018). And the interconnection level here is two-way.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…• on the regularities of development of strength, speed, coordination, endurance, and flexibility in children (Liakh, 2000;Khudolii, 2008;Serhiienko, Chekmarova, & Khadzhynov, 2012); • on the influence of the level of motor abilities development on building motor skills in schoolchildren (Ivashchenko, 2016;Ivashchenko, Prykhodko, & Cieslicka, 2018); • on the effectiveness of using tools and methods of training in motor abilities development (Liu, Chen, Ho, Fule, Chung, Shiang, 2013;Khudolii, Iermakov, & Prusik, 2015;Cieślicka, Ivashchenko, 2016). In previously published papers, it was found that the system of schoolchildren's physical education has a hierarchical structure where the development of motor abilities is subordinated to the process of building motor skills: strength development -development of movement coordination, speed, endurance, and flexibility -building motor skills (Khudolii, Ivashchenko, 2014;Ivashchenko, 2017;Ivashchenko, Khudolii, Iermakov, Lochbaum, Cieslicka, Zukow, Nosko, & Yermakova, 2016;Khudolii, Iermakov, & Prusik, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…• on the influence of the level of development of force on the process of learning the physical exercises of schoolchildren [5,11];…”
mentioning
confidence: 99%